American Board of Pediatrics-Based Pediatric Gastroenterology Curriculum - Joshua Noe; Robert Treat; Praveen Goday (Association of American Medical Colleges, 2015)
Abstract Introduction This curriculum was designed based on the American Board of Pediatrics (ABP) 2012 Content Outline to teach pediatric residents, as well as medical students, pediatric gastroenterology topics that a primary care pediatrician would be required to know for the ABP exam. Methods Using the 2012 ABP Content Outline for the general pediatrics board exam, we created a curriculum covering every pediatric gastroenterology topic. Topics were divided into 25 categories, and each category served as the basis for a concise, 10-minute lecture. One lecture was given by the ward attending physician on each nonholiday weekday over the course of a month to residents and students on their pediatric gastroenterology ward month, typically in the afternoon following patient rounds. This allowed all categories to be covered in a month. Learners who missed a session were expected to review the presentations, which were made available in the ward team's workroom. Results We performed a pre− and posttest analysis using 30 PREP questions (questions released by the ABP designed for self-assessment of board-eligible pediatricians). Our statistical analysis showed (1) improvement in mean overall scores and percentage of correct answers for pre− and posttest scores and (2) a moderately strong and statistically significant correlation in one-third of the questions between individual subjects' improvement and overall improvement as a group, suggesting that overall improvement in these test questions was due to the whole group of individuals improving, not just a handful of outlying high-performing individuals. Discussion This resource was created to allow academic centers to prepare pediatric residents for the ABP general pediatric exam. Considering that every topic the ABP requires a trainee to be familiar with is not always seen by a learner, complementary education is required. This curriculum was designed to ensure that trainees were exposed to all ABP-essential content topics. It is recommended that every 2 to 3 years, each session be assigned to a faculty member in the local gastroenterology division who can update the session with new literature or nationally recognized clinical recommendations that have been made into clinical practice.